The Hero - Wilber, Elaine; Orban, Paul, 1896-1974 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Hero" by Elaine Wilber is a science fiction novella written in the late 1950s. The story follows the crew of an Earth exploration ship, Ship UXB-69311, as they encounter the alien culture of the planet Engraham. The narrative centers around themes of heroism, human desire, and the absurdity of social conventions, particularly in the context of the crew's interactions with the native inhabitants. In the unfolding plot, the crew, composed of bored and restless men, deals with the absurdities of their situation$1 (Bnamely, their encounters with the beautiful but biologically unresponsive women of Engraham. The protagonist, Dick Blunt, attempts to impress a local woman named Catataphinaria while the rest of the crew grapples with their own frustrations and urges. As the story progresses, it becomes evident that the naive assumptions of the crew regarding the Engrahamites are dramatically turned on their heads when Catataphinaria reveals her intelligence and the societal structures of her people. This culminates in a twist that challenges the crew$1 (Bs expectations and their understanding of heroism, ultimately forcing them to confront the realities of their exploration and their place within it. The story provides a humorous yet insightful commentary on human nature, desire, and the consequences of colonialist attitudes. (This is an automatically generated summary.)s
Release date is 2011-04-04
Produced by Frank van Drogen, Greg Weeks, and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Human-alien encounters -- Fiction; Life on other planets -- Fiction